Subduction-related origin of eclogite xenoliths from the Wajrakarur kimberlite field, Eastern Dharwar craton, Southern India: Constraints from petrology and geochemistry. (1st October 2015) - Dongre, A.N.; Jacob, D.E.; Stern, R.A.
Abstract: Major and trace elements as well as the first oxygen isotopes are reported on eclogite xenoliths from the Mesoproterozoic KL2 and P3 kimberlite pipes of the Wajrakarur kimberlite field, Eastern Dharwar craton, Southern India. Garnets in kyanite-bearing samples are rich in grossular, whereas they are predominantly pyrope-almandines in the bimineralic (kyanite-free) samples. The kyanite eclogite from the P3 pipe is more Mg-rich than those from KL2 pipe. Equilibration temperatures indicate derivation from 4.5 to 5.3 GPa and 1060 to 1220 °C for the KL2 samples and 3.6 GPa, 918 °C for the P3 sample. Garnet rare earth element patterns show two characteristic types, one with relatively low and flat heavy rare earth element patterns: Wajrakarur Group 1 and a second with lower light to heavy rare earth element ratios: Wajrakarur Group 2. Most samples in Wajrakarur Group 1 show pronounced positive Eu anomalies in garnet and positive Eu and Sr anomalies in the reconstructed whole rock trace element patterns; these are among the strongest anomalies in eclogite xenoliths worldwide. In contrast, Wajrakarur Group 2 samples show only subtle positive Eu anomalies. Oxygen isotopic ratios of garnets range between +5.3‰ and +7.8‰ δ 18 O. This range extends significantly beyond the range for unchanged mantle. Similar to many other eclogite suites worldwide, the Wajrakarur Group 1 and Group 2 eclogite suites shows evidence for an origin as crustal gabbroic material, likely once part of the oceanic crust, which was subducted and imbricated under the Eastern Dharwar craton. Their surface origin therefore lends support to geodynamic models that favor amalgamation of the Dharwar craton by subduction.